NEW EMBO MEMBER'S REVIEW: Acetylation: a regulatory modification to rival phosphorylation? - Kouzarides, Tony (Oxford University Press, 2000)
The fact that histones are modified by acetylation has been known for almost 30 years. The recent identification of enzymes that regulate histone acetylation has revealed a broader use of this modification than was suspected previously. Acetylases are now known to modify a variety of proteins, including transcription factors, nuclear import factors and α–tubulin. Acetylation regulates many diverse functions, including DNA recognition, protein–protein interaction and protein stability. There is even a conserved structure, the bromodomain, that recognizes acetylated residues and may serve as a signalling domain. If you think all this sounds familiar, it should be. These are features characteristic of kinases. So, is acetylation a modification analogous to phosphorylation? This review sets out what we know about the broader substrate specificity and regulation of acetyl– ases and goes on to compare acetylation with the process of phosphorylation.